Upaya Peningkatan Pengetahuan Siswa Melalui Pendidikan Kesehatan Tentang Pertolongan Pertama Pada Kasus Kegawatdaruratan Sehari-Hari - Erlin Kurnia; Srinalesti Mahanani; Desi Natalia Trijayanti Idris; Fidiana Kurniawati (Pelita Abdi Masyarakat, 2022)
Background: First Aid is a rescue measure so that the victim's condition does not worsen before assistance from professional medical personnel arrives. Knowledge of first aid is very important for the public to know in dealing with emergencies. Many of us have encountered students who had an accident, whether it was broken bones, fainting, sprains, etc., who were given the same treatment and even made an error in giving help. This condition is of course very dangerous if it results in aggravating the patient's condition. This activity aims to increase students' knowledge of first aid in everyday emergency cases.Method: Community service activities are carried out in the form of Health Promotion using videos and webinars as an effort to improve the ability of high school students to perform first aid in daily emergencies.Result: At the end of the activity the participants experienced an increase in knowledge. It is hoped that similar activities can continue to be carried out to prevent an increase in morbidity and mortality rates in the communityConclusion: Health Promotion with Video and webinars can improve the ability of high school students to carry out first aid in daily emergencies correctly.